KTP Management Process In The Implementation Of The Population Administration System In Waigete District, Sikka District East Nusa Tenggara Province - Andi Risma Jaya; Susilawati Susilawati; Ruslimin Ruslimin; Nurmillah Ilyas; Yurniati Yurniati (Public Resource Innovation Management and Excellence, 2025)
The performance of public services carried out by government officials in various service sectors, especially those involving the fulfillment of civil rights and basic community needs, is still far from expected. This research aims to determine the process of ID card processing services in Waigete District, Sikka Regency and to determine the factors that influence the ID card service process in Waigete District, Sikka Regency. This researcher uses a qualitative descriptive analysis method from data obtainedthrough in-depth interviews with selected respondents. . The results of this research show that the administrative policy in ID card services in Waigete sub-district, Sikka Regency has implemented number 24 of 2013 and number 52 of 2016 in accordance with applicable regulations and provides direction to the public regarding the rules or procedures that have been established by the Regent of Sikkka in